ANALYSIS OF APPROACHES TO «EDUCATIONAL MEDIA SPACE» DEFINITION - Oksana V. Belitskaya (Открытое образование (Москва), 2016)
The article covers directions of researches in the field of educational media space. The essence of the concept is considered within the following approaches: system, the mental and emotional, personal and developing, the competence-based, social-geographic, distance, and local.